Bombesin-like receptor 3 (Brs3) expression in glutamatergic, but not GABAergic, neurons is required for regulation of energy metabolism - Cuiying Xiao; Ramón A. Piñol; Jesse Lea Carlin; Cuiling Li; Chuxia Deng; Oksana Gavrilova; Marc L. Reitman (Elsevier, 2017)
Objective: Bombesin-like receptor 3 (BRS-3) is an orphan G protein-coupled receptor. Brs3 null mice have reduced resting metabolic rate and body temperature, increased food intake, and obesity. Here we study the role of Brs3 in different neuron types. Methods: Mice able to undergo Cre recombinase-dependent inactivation or re-expression of Brs3 were generated, respectively Brs3fl/y and Brs3loxTB/y. We then studied four groups of mice with Brs3 selectively inactivated or re-expressed in cells expressing Vglut2-Cre or Vgat-Cre. Results: Deletion of Brs3 in glutamatergic neurons expressing Vglut2 reproduced the global null phenotype for regulation of food intake, metabolic rate, body temperature, adiposity, and insulin resistance. These mice also no longer responded to a BRS-3 agonist, MK-5046. In contrast, deletion of Brs3 in GABAergic neurons produced no detectable phenotype. Conversely, the wild type phenotype was restored by selective re-expression of Brs3 in glutamatergic neurons, with no normalization achieved by re-expressing Brs3 in GABAergic neurons. Conclusions: Brs3 expression in glutamatergic neurons is both necessary and sufficient for full Brs3 function in energy metabolism. In these experiments, no function was identified for Brs3 in GABAergic neurons. The data suggest that the anti-obesity pharmacologic actions of BRS-3 agonists occur via agonism of receptors on glutamatergic neurons.